Point of View in Malay Fiction: (Sudut Pandangan dalam Cereka Melayu) (Jurnal Bahasa, 2021)
Point of view is one of the ways an author to visualizes what is heard or seen by a character in a piece of fiction. Usually, point of view is presented through pronouns and modalities. This study investigates the use of both markers in Malay fiction. Aspects of pronouns are analysed from the point of view of subjectivity and objectivity, while the aspect of modality is discussed in terms of its form and meaning in the text. This is because the limitations of the author's knowledge can be assessed through the presence of pronouns and modalities. For this purpose, this study will use some examples of Malay-language fiction to describe the strategy of using pronouns and modalities. To identify the category and meaning of modality, this study applies the category of modality proposed by Halliday (1994). The findings show that the third person point-of-view functions to describe the author's omniscience, while the first-person point-of-view portrays limited knowledge. The use of modality in Malay literature also varies. For example, barangkali (may), mungkin (perhaps) and boleh jadi (maybe) serve to illustrate the limitations of author's knowledge, while mesti (must) and perlu (need) show the author's omniscience. In addition, this study also found that the truth of a proposition varies according to the category of modality.Keywords: Pronoun, modality, point of view, subjectivity, objectivity